2011
DOI: 10.4049/jimmunol.1003482
|View full text |Cite
|
Sign up to set email alerts
|

EphB Receptors Trigger Akt Activation and Suppress Fas Receptor-Induced Apoptosis in Malignant T Lymphocytes

Abstract: Treatment of hematopoietic malignancies often requires allogeneic bone marrow transplantation, and the subsequent graft-versus-leukemia response is crucial for the elimination of malignant cells. Cytotoxic T lymphocytes and NK cells responsible for the immunoelimination express Fas ligand and strongly rely on the induction of Fas receptor-mediated apoptosis for their action. Although cancer cells are removed successfully by graft-versus-leukemia reactions in myeloid malignancies, their efficiency is low in T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 84 publications
(131 reference statements)
0
24
0
Order By: Relevance
“…EphB3 kinase activation can also inhibit Akt, which leads to suppression of non-small-cell lung cancer migration and metastasis, by promoting the assembly of a complex involving the EphB3 binding partner RACK1 (receptor for activated C-kinase 1), the serine/threonine phosphatase PP2A and Akt itself (Li et al 2012). However, Eph receptors can also activate Akt, for example in pancreatic cancer cells stimuated with ephrin-A1 (Chang et al 2008) or in malignant T lymphocytes where ephrin-B treatment suppresses apoptosis (Maddigan et al 2011). …”
Section: Eph Receptor Forward Signalingmentioning
confidence: 99%
“…EphB3 kinase activation can also inhibit Akt, which leads to suppression of non-small-cell lung cancer migration and metastasis, by promoting the assembly of a complex involving the EphB3 binding partner RACK1 (receptor for activated C-kinase 1), the serine/threonine phosphatase PP2A and Akt itself (Li et al 2012). However, Eph receptors can also activate Akt, for example in pancreatic cancer cells stimuated with ephrin-A1 (Chang et al 2008) or in malignant T lymphocytes where ephrin-B treatment suppresses apoptosis (Maddigan et al 2011). …”
Section: Eph Receptor Forward Signalingmentioning
confidence: 99%
“…Previous reports, including the work of our group, have shown that some receptors of the EphB type suppress apoptotic responses triggered by death receptors [20-22, 31]. Since earlier work shows that EPHB6 often executes its responses through interactions with other EphB receptors [29, 32, 33], we examined if it also interferes with DR5-induced apoptosis in cancer cells.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, we have not observed the pro-apoptotic effect of EPHB6 expression in our experiments with paediatric T-cell acute lymphoblastic leukaemia (T-ALL) cells (data not shown), which further confirms the specificity of our observations in TNBC cells and indicates that the pro-apoptotic EPHB6 action via DRP1 activation may be restricted to certain types of malignancies. This distinction could be due to the fact that EphB receptors, including EphB6, act in T-ALL cells in a completely different molecular context, which collectively allows them to activate the AKT kinase, initiating anti-apoptotic signaling and supporting cell survival [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation by Ephrin-A1, EphA2 behaves as an upstream negative regulator of Akt, resulting in the inhibition of cell migration [111]. Interestingly, the PI3K/Akt and mitogenactivated protein kinase (MAPK) pathways are also important in other functions of Ephs and Ephrins such as cell death and autophagy [112][113][114][115], suggesting a complex but precise coordination. The analysis of transgenic mice models of mammary carcinomas where EphA2-deficiency and ErbB2 overexpression were combined, suggests that EphA2 cooperates with ErbB2 to promote tumor and metastatic progression.…”
Section: Phosphorylation and Kinase-dependence Of Eph/ephrin Signalinmentioning
confidence: 98%